'Alcohol short-circuits important part of the brain': Swedish newspaper representations of biomedical alcohol research. (4th May 2017) - Bogren, Alexandra
Abstract: The media has a central role in communicating and constructing health knowledge, including communicating research findings related to alcohol consumption. However, research on news reporting about alcohol is still a relatively small field; in particular, there are few studies of the reporting of biomedical alcohol and drug research, despite the assumed increasing popularity of biomedical perspectives in public discourse in general. The present article addresses the representational 'devices' used in Swedish press reporting about biomedical alcohol research, drawing on qualitative thematic analysis of the topics, metaphors, and optimist versus critical frames used in presenting biomedical research findings. In general, the press discourse focuses on genetic factors related to alcohol problems, on the role of the brain and the reward system in addiction, and on medication for treating alcohol problems. Metaphors of 'reconstruction' and 'reprograming' of the reward system are used to describe how the brain's function is altered in addiction, whereas metaphors of 'undeserved reward' and 'shortcuts' to pleasure are used to describe alcohol's effects on the brain. The study indicates that aspects of the Swedish press discourse of biomedical alcohol research invite reductionism, but that this result could be understood from the point of view of both the social organization of reporting and the intersection of reporting, science, and everyday understandings rather than from the point of view of the news articles only. Moreover, some characteristics of the media portrayals leave room for interpretation, calling for research on the meanings ascribed to metaphors of addiction in everyday interaction.